Effects of borrower-based regulation on housing demand - Rikke Rhode Nissen; Alessandro Tang-Andersen Martinello; Simon Juul Hviid; Christian Sinding Bentzen (Danmarks Nationalbank, 2022)
Borrower-based regulation, influencing housing buyers' access to credit, would have different effects depending on buyer's demographics, wealth and location. By modelling housing buyers' preferences and budget constraints, we find that any such regulation would push demand to suburban areas. Limits on debt-to-income ratios (DTI) would mainly affect buyers in the largest cities; however, we find that the restrictions would not affect net demand for small apartments in Copenhagen.
Keywords: 330